Private finance for climate-change adaptation: challenges and opportunities for Kenya - Pieter Pauw; Adis Dzebo (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Private investments in climate-change adaptation are important. First, because the costs of adaptation are too high to be met by the public sector alone. And second, developed countries pledged to mobilise USD 100 billion annually by 2020 to support developing countries' climate change mitigation and adaptation; the private sector is described as a source of finance. Yet how realistic is it to rely on the mobilisation of private investments in adaptation, in particular for less developed countries? This Policy Brief aims to answer this question in relation to Kenya. It is based on interviews and an analytical framework that spells out enabling environments; mobilisation and delivery of private investments (see Figure 1). As a first step, developing and developed countries, and the private sector can create enabling environments to mobilise private investments in adaptation. Adaptation is a priority to both the Kenyan government and its development partners. However, private adaptation has not been mainstreamed in key government policies. The Kenyan private sector appears unfamiliar with the concept of adaptation. Where it acts on adaptation, its purpose is generally resource efficiency or to address land degradation. This makes it hard to track mobilised private investments. For example, rural communities might contribute to adaptation though improved water management. However, related expenditure remains unknown, as is the extent to which it is financed by banks. Neither actor tracks or reports investments in adaptation. It is even harder to assess if private investments, once mobilised, actually deliver on adaptation. Regardless of the underlying motivations, many investments that reduce poverty or stimulate sustainable resource use contribute to adaptation. However, a private actor can also adapt at the expense of communities, for example by securing or fencing off its own water intake. There are no explicit checks and balances on private-sector impacts on adapta¬tion. Safeguards such as environmental impact assessments (EIAs) do not explicitly address adaptation. All of the above make it extremely difficult to assess private investments in adaptation in Kenya, in particular in the context of the above-mentioned USD 100 billion target. Kenya's private sector has taken little interest in the UN climate negotiations. It is currently not able to tap into international funds such as the Green Climate Fund. If it could, private actors might take more interest in adaptation and the UN negotiations. This in turn might also provide incentives for quantifying investments in adaptation. The Kenyan government could encourage more private-sector investments in adaptation. By stimulating a shared public-private awareness and understanding of adaptation, the government could improve enabling environments for private adaptation; mobilise more private investments; and improve the tracking of private investments in adaptation. Moreover, the government and development partners could include adaptation criteria in project selection and EIAs in order to reduce private maladaptation and increase private adaptation.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Klimawandel